MECHANISMS FOR ENSURING THE PSYCHOLOGICAL SECURITY OF YOUTH INFORMATION IN SOCIAL NETWORKS - Erkinov Javohir Latif ugli (American Journals Publishing, 2023)
The article examines the essence and nature of information and psychological influence on a person, analyzes the forms of influence, including destructive ones. Their active use in the Internet environment raises the question of the need for the formation and development of information and psychological security of the individual based on the management of social attitudes of a young person on the Internet.
Keywords: Information, ICT, psychology, social network, informational and psychological security, Internet, computer.